The GlyT1 Inhibitor Bitopertin Ameliorates Allodynia and Hyperalgesia in Animal Models of Neuropathic and Inflammatory Pain - Armbruster, Anja; Neumann, Elena; Kötter, Valentin; Hermanns, Henning; Werdehausen, Robert; Eulenburg, Volker (Frontiers in Molecular Neuroscience, 2018)
Background: Chronic pain conditions are difficult to treat and the therapeutic outcome is frequently unsatisfactory. Changes in excitation/inhibition balance within the dorsal horn contribute to the establishment and persistence of chronic pain. Thus, facilitation of inhibitory neurotransmission is a promising approach to treat chronic pain pharmacologically. Glycine transporter 1 (GlyT1) plays an important role in regulating extracellular glycine concentrations. Aim of the present study therefore was to investigate whether the specific GlyT1 inhibitor bitopertin (RG1678; RO4917838) might constitute a novel treatment for chronic pain by facilitating glycinergic inhibition. Methods: Mechanical allodynia and thermal hyperalgesia were induced by chronic constriction injury of the sciatic nerve or carrageenan injections into the plantar surface of the hind paw in rodents. The effect of acute and long-term bitopertin application on the reaction threshold to mechanical and thermal stimuli was determined. General activity was determined in open field experiments. The glycine concentration in cerebrospinal fluid and blood was measured by HPLC. Results: Systemic application of bitopertin in chronic pain conditions leads to a significant increase of the reaction thresholds to mechanical and thermal stimuli in a time and dose-dependent manner. Long-term application of bitopertin effectuated stable beneficial effects over four weeks. Bitopertin did not alter reaction thresholds to stimuli in control animals and had no effect on general locomotor activity and anxiety but lead to an increased glycine concentration in cerebrospinal fluid. Conclusion: These ﬁndings suggest that inhibition of the GlyT1 by bitopertin represents a promising new approach for the treatment of chronic pain.